Glycerol/starch/Na+-montmorillonite nanocomposites: A XRD, FTIR, DSC and 1H NMR study - Liu, Huihua; Chaudhary, Deeptangshu; Yusa, S.; Tade, Moses (Elsevier, 2011)
We studied the influence of glycerol/MMT loading on the nanocomposites morphology prepared from amylose starch biopolymer with various glycerol/MMT (Na+-montmorillonite) concentrations. Samples were studied by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and proton nuclear magnetic resonance (1H NMR) measurements. XRD results highlighted the impact of glycerol on the MMT exfoliation; with 15% glycerol imposed the largest inter-lamella spacing (d-spacing) value. Newly formed hydrogen bonds and the interaction among starch/glycerol/MMT were evidenced by peaks associated with –OH stretching located at 3300cm−1 and 999cm−1 from the FTIR spectra. DSC measurements revealed that glass transition temperature (Tg) decreased with increasing glycerol content. MMT also lowered the crystallization temperature (Tm) and suppressed the overall sample crystallinity. Proton NMR spectra obtained at 25 ◦C and 70 ◦C from samples containing only starch and glycerol provided important clues for explaining the starch and glycerol interaction.